If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 7 + 6x + -9 = 62 Reorder the terms: 7 + -9 + 4x + 6x = 62 Combine like terms: 7 + -9 = -2 -2 + 4x + 6x = 62 Combine like terms: 4x + 6x = 10x -2 + 10x = 62 Solving -2 + 10x = 62 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 10x = 62 + 2 Combine like terms: -2 + 2 = 0 0 + 10x = 62 + 2 10x = 62 + 2 Combine like terms: 62 + 2 = 64 10x = 64 Divide each side by '10'. x = 6.4 Simplifying x = 6.4
| 3h(2+3j)+2j(2h+3)= | | 40.00x+25x=40.00x | | 4y=5x+3 | | 3x-8y=-13 | | 13x-9x+7-x=10 | | 8.77-x=3.44 | | 0.8(120)= | | 8.125-x=3.44 | | 6(x-3)-5(x+3)=5-x | | 7x+5=4x+15+3x | | 6x-2=3x+12 | | 12x+3=9x+21 | | 2000=150+225*3.50x | | 2000=150+225*3.50 | | 90=15*x-3 | | 90=15(x)-3 | | (-1)*b=0 | | 3.5x-1=0.5(7x+2) | | f(x)81x^2-100=0 | | x=1x^2+13x+40 | | 6(3a-b)-6(5b-7a)= | | (x)=1x^2+5x-50 | | X+.071=3 | | f(x)=1x^2+5x-50 | | x=1x^2-9x+14 | | 5(k+1)=16 | | f(x)=1x^2-9x+14 | | x+.07=3 | | 0.6666667y+6=y | | 3t+8(2t-6)=16-4(v+7) | | 11x-9y=14 | | f(x)=5cosx |